QLTI-11. IMPROVING ACUTE STROKE RESPONSE AT A COMPREHENSIVE CANCER CENTER: A MULTIDISCIPLINARY HOSPITAL-BASED QUALITY IMPROVEMENT PROJECT. (14th November 2022) - Quashie, Wayne; Avila, Edward; Barzola, Melissa; Buchholz, Tara; Majeed, Jibran; Maria, Nicole Santa; Schaff, Lauren
Abstract: BACKGROUND: Stroke is common in patients with malignancy, but cancer patients in treatment have contraindications to intravenous (IV) tissue plasminogen activator (tPA). Advancements in endovascular therapy (EVT) has expanded options for acute stroke management . Memorial Sloan Kettering (MSK) is a cancer center without a public emergency room. Acute stroke management occurs inpatient or in urgent care center (UCC). We determined a need for rapid identification and management for acute strokes in our patient population. METHODS: We developed a multidisciplinary Acute Stroke Pathway relying on activation of our hospital's rapid response team (RRT), neurology, radiology, nursing support, patient escort services, and pharmacy. We initiated hospital-wide education around stroke symptoms and the pathway. All stroke activations are reviewed by Neurology bi-weekly for real-time feedback. Metrics include the times of symptom identification ("door time" = UCC check in or symptom discovery for inpatients), evaluation, head computed tomography (CT), labs, and administration of IV tPA. Times are compared to our 2016 institutional baseline data and National Institute of Neurological Disorders and Stroke (NINDS) benchmarks. RESULTS: Since implementation of the pathway (6/11/2018) through Q1 2022 (3/31/2022), there were 551 acute stroke activations, 13 IV tPA administrations, and 48 patients transferred to a comprehensive stroke center for consideration for EVT. Average 2021 door-to-evaluation time: 8 mins (baseline: 18 mins, NINDS: 10 mins), door-to-stroke team: 11 mins (baseline: unknown, NINDS: 15 mins), door-to-CT: 33 mins (Baseline: 95 mins, NINDS: 25min), door-to-CT interpretation: 34 mins (baseline: 251 mins, NINDS: 45 mins), door-to-labs: 50 mins (baseline: unknown, NINDS: 45 min), door-to-IV tPA: 62 mins (baseline: unknown, NINDS: 60min). DISCUSSION: The patient population at MSK is distinct from most hospitals. Patients with cancer have a higher incidence of stroke but are unlikely candidates for intervention. Inter-professional collaboration resulted in early stroke care in oncology patients consistent with NINDS benchmarks.